2007
DOI: 10.1017/s0007114507750869
|View full text |Cite
|
Sign up to set email alerts
|

Gonadectomy and high dietary fat but not high dietary carbohydrate induce gains in body weight and fat of domestic cats

Abstract: A high concentration of dietary carbohydrate is suggested to increase the risk of obesity and diabetes mellitus in domestic cats. To evaluate this, food intake, body weight, fat mass and circulating adiposity-related factors were determined in twenty-four sexually mature (9-12 months) cats assigned to four six-cat dietary groups balanced for body weight and sex. The effect of dietary fat in exchange for carbohydrate at 9, 25, 44 and 64 % of metabolisable energy (ME) in a purified diet of constant protein:ME ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
3
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 40 publications
5
77
3
6
Order By: Relevance
“…Food intake and BW increased in all cats following ovariohysterectomy, as has been noted in other studies (Fettman et al, 1997;Harper et al, 2001;Kanchuk et al, 2003;Nguyen et al, 2004;Backus et al, 2007;Cave et al, 2007;Belsito et al, 2009). Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 62%
“…Food intake and BW increased in all cats following ovariohysterectomy, as has been noted in other studies (Fettman et al, 1997;Harper et al, 2001;Kanchuk et al, 2003;Nguyen et al, 2004;Backus et al, 2007;Cave et al, 2007;Belsito et al, 2009). Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 62%
“…When 22 shorthair adult female cats were fed at maintenance energy requirements for intact cats before and after ovariohysterectomy, all the cats increased body weight by 16% and BCS by one point after ovariohysterectomy (Mitsuhashi et al 2011). Several studies in cats have also reported a significant increase in food intake after neutering, which leads to weight gain and decreased physical activity (Fettman et al 1998;Kanchuk et al 2003;Backus et al 2007;Belsito et al 2009). …”
Section: Sex and Reproductive Statusmentioning
confidence: 99%
“…The authors speculated that fatty acid may be used as a substitute for glucose to supply energy in high-fat diets. However, another study demonstrated that plasma concentrations of insulin in cats given the highest-fat diet were greater than those of cats given lower-fat diets [4]. The M/D dry diet (highest fat content in the present study) did not induce postprandial hyperglycemia or any apparent insulin secretion, leading us to speculate that dietary fat content has less impact and effect on postprandial glucose and insulin concentration, as compared with dietary carbohydrate and fiber content in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…However, according to previous studies, low-carbohydrate diets may also aid glycemic control in Type 2 DM by reducing hyperglycemia and aiding in recovery from glucose toxicity [1,13,27]. Several studies have employed a test meal, for evaluating postprandial glucose concentrations, insulin concentrations or changes in body weight [4,19,20,37]. However, information on the effects of the use of commercially available prescription diets to manage feline obesity is scarce and thus far includes only two studies that have investigated the effects of these diets on glucose and insulin concentrations in cats [8,26].…”
mentioning
confidence: 99%